Weathering Shakespeare: quando il clima si fa teatro - Forlini, Francesca (Mimesis Journal, 2021)
The article provides an overview of Evelyn O’Malley’s timely volume Weathering Shakespeare. Audiences and Open-air Performance (2021). Drawing on audience accounts of outdoor productions of Shakespearean plays, the book delves into the ways in which performers and audiences alike have reacted to unpredictable natural environments. Discussing O’Malley’s innovative approach to new and emerging performance practices, the article argues for a more conscious and ecologically aware perspective in theater studies, encouraging a deeper understanding of the interplay between nature, performance, and audience reception.